2016
DOI: 10.1002/cphc.201600425
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Dynamics in the Endoplasmic Reticulum of a Live Cell: Time‐Resolved Confocal Microscopy

Abstract: Fluorescence dynamics in the endoplasmic reticulum (ER) of a live non-cancer lung cell (WI38) and a lung cancer cell (A549) are studied by using time-resolved confocal microscopy. To selectively study the organelle, ER, we have used an ER-Tracker dye. From the emission maximum (λmaxem) of the ER-Tracker dye, polarity (i.e. dielectric constant, ϵ) in the ER region of the cells (≈500 nm in WI38 and ≈510 nm in A549) is estimated to be similar to that of chloroform (λmaxem =506 nm, ϵ≈5). The red shift by 10 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…34,[45][46]49 It revealed that the intracellular biomembranes are significantly more polar (less ordered) than plasma membranes. 46 Second approach exploited specific targeting of solvatochromic dyes to organelle of interest, 5,25,[35][36][50][51][52][53] including mitochondria 32,50,54 and ER. 35 However, these studies were focused on targeting one particular organelle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,[45][46]49 It revealed that the intracellular biomembranes are significantly more polar (less ordered) than plasma membranes. 46 Second approach exploited specific targeting of solvatochromic dyes to organelle of interest, 5,25,[35][36][50][51][52][53] including mitochondria 32,50,54 and ER. 35 However, these studies were focused on targeting one particular organelle.…”
Section: Introductionmentioning
confidence: 99%
“…46 Second approach exploited specific targeting of solvatochromic dyes to organelle of interest, 5,25,[35][36][50][51][52][53] including mitochondria 32,50,54 and ER. 35 However, these studies were focused on targeting one particular organelle. Specific targeting of different organelles using a family of probes based on the same solvatochromic dye would enable direct comparison of properties of organelles and their response to different stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…er provides a quality control system, regulating the modification and folding of membrane and secretory proteins and eliminating misfolded polypeptides through autophagic degradation or er-associated degradation (41). a variety of toxic insults including ca 2+ overload, failure of protein folding, synthesis, degradation or transport and hypoxia can interrupt the er function and give rise to erS (42).…”
Section: Discussionmentioning
confidence: 99%
“…The HeLa cells were grown in phenol red free DMEM (Dulbecco's Modified Eagle Medium) with 10 % fetal bovine serum, 1 % Pen Strep Glutamine (from Gibco) in an atmosphere of 5 % (v/v) CO 2 enriched air at 37 °C, as described earlier elsewhere . For microscopy, a T25 flask have been utilized for the purpose of culture the cells.…”
Section: Methodsmentioning
confidence: 99%